Historia i perspektywy rozwoju Katedry Geotechniki i Budowli Inżynierskich Politechniki Łódzkiej - Lefik, Marek; Sztromajer, Zofia (Wydawnictwo Politechniki Łódzkiej, 2011)
W artykule przedstawiono krótko ponad pięćdziesięcioletnią historię Katedry Geotechniki i Budowli Inżynierskich Politechniki Łódzkiej. Omówiono podstawowe tematy działalności naukowej, scharakteryzowano zespoły i osoby, które te badania prowadzą. Opisano prace habilitacyjne zakończone i przygotowywane w Katedrze. Artykuł kończą prognozy i wnioski dotyczące rozwoju Katedry.

In the paper a short review of the over fifty years history of the Department of Geotechnics and Engineering Structures of Technical University of Łódź is given. Main subjects of the scientific activity of the Department are discussed, the scientific staff of the department is presented. Details concerning the accomplished and being currently under preparation, doctoral and habilitation thesis, are outlined. The paper ends with conclusions characterizing main directions of the future developments of the Department.
History and development perspectives of the Department of Geotechnics and Engineering Structures of the Technical University of Łódź